Breakfast Ideas - Claudia Peñuela (EDIS)
FCS8931, a 1-page illustrated fact sheet by Claudia Peñuela, provides a chart for making unique and nutritious breakfast combinations. Published by the UF Department of Family, Youth and Community Sciences, October 2010.